Perilaku Sosial Anak Usia 5-6 Tahun di Taman Kanak-kanak Ekasakti Padang - Ilmi, Miftahul; Marlina, Serli (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2019)
The purpose of this study was to describe the social behavior of children aged 5-6 years in the Ekasakti Kindergarten, Padang Barat District, Padang City. This type of research is qualitative research with descriptive methods. Researchers use principals and teachers as research informants. The researcher collects data by means of observation, interviews, and documentation. The data analysis technique is done using data triangulation techniques. Social behavior of children aged 5-6 years in Ekasakti Kanak-Kanak Kanak Padang Barat City, Padang City can be observed in all activities carried out by children from, such as when their first child arrives at school, when marching, studying in class and when children play outside the classroom . The results showed various forms of social behavior in children aged 5-6 years such as imitating behavior, competition, cooperation, sympathy, empathy, social support, sharing and familiar behavior. Suggestions from researchers to parents and teachers to be able to teach children to behave well, and become a good example for children.